2013
DOI: 10.1016/j.whi.2012.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability and Usability of Self-Collected Sampling for HPV Testing Among African-American Women Living in the Mississippi Delta

Abstract: Background HPV DNA testing has been shown to be an effective approach to cervical cancer screening, and self-collection sampling for HPV testing could be a potential alternative to Pap test, provided that women who tested positive by any method get timely follow-up and care. This feasibility study examined acceptability and usability of self-collected sampling for HPV testing among African American (AA) women in the Mississippi Delta in order to inform the development of interventions to promote cervical cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
55
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 45 publications
9
55
1
Order By: Relevance
“…Our findings are consistent with previous findings that willingness to self-sample for HPV was a determinant of future HPV self-sampling [9]. Willingness to self-sample for HPV is a logical predictor for likelihood of HPV selfsampling because without willingness, a health behavior will not occur [30].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings are consistent with previous findings that willingness to self-sample for HPV was a determinant of future HPV self-sampling [9]. Willingness to self-sample for HPV is a logical predictor for likelihood of HPV selfsampling because without willingness, a health behavior will not occur [30].…”
Section: Discussionsupporting
confidence: 92%
“…Cervical cancer screening has traditionally been done by physicians using the Pap test, which many women perceive as uncomfortable and embarrassing [3][4][5][6][7]. A potential alternative to the Pap test in Western countries has been vaginal self-sampling for human papillomavirus (HPV) [5,8,9], the causative agent for most cervical cancers [10]. HPV self-sampling is easy to perform, less painful, less embarrassing, and less anxiety provoking than the Pap test [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the cost of testing may discourage patients from choosing to screen for HPV (Oranratanaphan et al, 2014). To improve screening coverage, self-administered sample collection could be an alternative to Pap smear test (Nilyanimit et al, 2013;Scarinci et al, 2013). Previous studies examined the sensitivity and predictive value of HPV detection by comparing self-collected and physician-collected samples for HPV screening.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that using self-sampling method increases participation of non-responders in screening programs (Bosgraaf et al, 2014a;Piana et al, 2011;Sancho-Garnier et al, 2013). Self-sampling samples have also been shown to be suitable for HPV testing (Sancho-Garnier et al, 2013;Scarinci et al, 2013;Tamalet et al, 2013;Othman and Othman, 2014) even in a in a large-scale (Harper et al, 1999).…”
Section: Self-collection Tools For Routine Cervical Cancer Screening:mentioning
confidence: 99%
“…Self-sampling is more attractive for the non-attendees in countries which have organized screening and from rural women in countries which have limited resources (Sancho-Garnier et al, 2013). It can be an alternative method to women who are reluctant to undergo pelvic examination due to shyness (Scarinci et al, 2013) or too busy looking after the family which is often the case amongst Asian women (Othman and Rebolj, 2009). In addition, it may reduce cost on the 'patients' and on 'hospitals' as no visits to clinicians are needed (Darlin et al, 2013;Scarinci et al, 2013).…”
Section: Advantages and Limitations Of Self-samplingmentioning
confidence: 99%